Ethno-performance in Spisz (p. 1) - Barański, Janusz (Literatura Ludowa. Journal of Folklore and Popular Culture, 2024)
The subject of the article are two regional events, a competition and a review of the folklore of Polish Spisz: Spiskie Zwyki and Spiska Watra. They are organized each year, respectively, in winter and summer at the Dunajec Castle in Niedzica and in the Communal Cultural Center in Łapsze Niżne with its seat in Niedzica. The discussed region is a small fragment of a historical land, the main par of which is located in the territory of Slovakia. It was part of the Kingdom of Hungary for hundreds of years, hence its specificity and cultural identity. In the light of ethnographic research, the analyzed events belong to ethno-performance practices that combine artistic and social aspects. The first is an expression of regional aesthetics and artistry (verbal and musical folklore, dance, regional costume), the second – of the ritual nature of events serving identity processes. In the light of the findings, the discussed cases of ethno-performance represent cultural legacy in the mode of heritage. In this sense, they are a form different from the older tradition and can be considered a kind of metacultural practice and metacultural commentary on regional culture.